Factor the polynomial. Multiply the factors to check your answer.
5x(x+7)-(7+x)

Question

Asked 5/18/2014 7:50:26 PM

Updated 5/18/2014 11:10:52 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by yeswey [5/18/2014 11:06:36 PM]

selymi|Points 14936|

Question

Asked 5/18/2014 7:50:26 PM

Updated 5/18/2014 11:10:52 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by yeswey [5/18/2014 11:06:36 PM]

Rating

3

5x(x + 7) - (7 + x)

= 5x^2 + 35x - 7 - x

= 5x^2 + 34x - 7

= (x + 7)(5x - 1)

To check the answer by multiplication:

(x + 7)(5x - 1)

= 5x^2 - x + 35x - 7

= 5x^2 + 34x - 7

= 5x^2 + 35x - x - 7

= 5x(x + 7) - (x + 7)

= 5x^2 + 35x - 7 - x

= 5x^2 + 34x - 7

= (x + 7)(5x - 1)

To check the answer by multiplication:

(x + 7)(5x - 1)

= 5x^2 - x + 35x - 7

= 5x^2 + 34x - 7

= 5x^2 + 35x - x - 7

= 5x(x + 7) - (x + 7)

Added 5/18/2014 11:10:52 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/19/2014 3:24:47 AM]

What pattern is represented by the polynomial 4x^2+12x+9?
A.
difference of two squares
B.
general trinomial
C.
perfect square trinomial
D.
prime trinomial **Weegy:** The polynomial 4x^2+12x+9 represents perfect square trinomial.
4x^2+12x+9 = (2x + 3)^2 (More)

Question

Expert Answered

Updated 5/19/2014 12:27:26 AM

0 Answers/Comments

29,943,333

questions answered

There are no comments.